The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021 36th IEEE/ACM International Conference on Automated Software Engineering (ASE) 2021
DOI: 10.1109/ase51524.2021.9678785
|View full text |Cite
|
Sign up to set email alerts
|

IFIZZ: Deep-State and Efficient Fault-Scenario Generation to Test IoT Firmware

Abstract: IoT devices are abnormally prone to diverse errors due to harsh environments and limited computational capabilities. As a result, correct error handling is critical in IoT. Implementing correct error handling is non-trivial, thus requiring extensive testing such as fuzzing. However, existing fuzzing cannot effectively test IoT error-handling code. First, errors typically represent corner cases, thus are hard to trigger. Second, testing error-handling code would frequently crash the execution, which prevents fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…From a technical perspective, vulnerabilities in IoT FW are mainly caused by input-independent errors (e.g., memory exhaustion) rather than input-dependent errors (e.g., invalid parameters) as is the case in PCs. [28] examines the firmware of 10 routers and IoT devices and finds 109 errors in total.…”
Section: Related Work 21 the Need For Updates And Patches Of Internet...mentioning
confidence: 99%
“…From a technical perspective, vulnerabilities in IoT FW are mainly caused by input-independent errors (e.g., memory exhaustion) rather than input-dependent errors (e.g., invalid parameters) as is the case in PCs. [28] examines the firmware of 10 routers and IoT devices and finds 109 errors in total.…”
Section: Related Work 21 the Need For Updates And Patches Of Internet...mentioning
confidence: 99%
“…(2) Recent studies [18,50] have identified the need for certain registers to repeatedly report specific values in order to execute firmware correctly and chosen to fix register values (use immutable inputs). But, fixing the values of registers effectively over restricts the search-space and can prevent testing of error handlers; importantly, error handlers were identified as a common source of bugs [23,28]. Expounding upon this insight we propose the peripheral input playback technique to: i) exploit the knowledge that many peripheral registers often repeatedly return the same value under typical execution conditions; and ii) benefit from mutated inputs to overcome restrictions on triggering of error handlers.…”
Section: An Overview Of Our Approachmentioning
confidence: 99%
“…For example, bits within a serial port status register, such as the parity error, could be triggered by a malicious actor, resulting in the execution of the associated error handler. Notably, IFIZZ [28], previously identified error handlers as a common source of bugs, with more than 25% of patches for some programs commonly used on routers containing changes to error handlers. • Third, new models may need to be generated during fuzzing as the corresponding peripherals are discovered, complicating the fuzzing process.…”
Section: Our Approachmentioning
confidence: 99%